Situs Makam-Makam Kuna di Kabupaten Kuningan Bagian Timur: Kaitannya dengan Religi - Effie Latifundia (Kapata Arkeologi, 2016)
Site of ancient tombs in the eastern part of Kuningan regency, West Java shows the indication of religion and tradition. This is reflected in the lives of the communities  that adopted the practice of honoring the well known figures of the past. The graves of these famous figures such as religious leaders, community leaders, ancestors receive certain treatments. The ancient tombs have been seen as the sacred site, as well as an object of pilgrimage, and used as the media to ask for something to include offerings. This paper aims to uncover these ancient tombs with their religious background. The data have been collected  by a survey to gain information and describe the forms of ancient tombs. The results showed  that although Islam flourishes, the belief in ancestors as religion before Islam still ongoing and sustained. Essentially any form of tribute to the ancestors is a continuation of the megalithic tradition in prehistoric times. It was concluded, at the time of the influence of Islamic religious life particularly associated with death there is a reduction in pre-Islamic era.Situs makam-makam kuna di Kabupaten Kuningan bagian timur, Jawa Barat menunjukkan adanya unsur religi dan tradisi. Hal ini tercermin dalam kehidupan sebagian masyarakat adanya suatu konsep penghormatan kepada tokoh yang sudah meninggal dunia. Makam para tokoh terkenal  seperti  pemuka agama, tokoh masyarakat, leluhur mendapat perlakuan tertentu. Makam-makam kuna tersebut dikeramatkan, sebagai objek ziarah, dan dijadikan media meminta sesuatu dengan dilengkapi sesaji. Tulisan ini bertujuan mengungkap makam-makam kuna berlatar religius. Metode pengumpulan data dilakukan dengan survei untuk mengumpulkan informasi dan mendeskripsikan bentuk-bentuk makam kuno. Hasil penelitian menunjukkan meskipun Islam berkembang namun kepercayaan terhadap leluhur sebagai religi sebelum Islam masih terus berlangsung dan dipertahankan. Secara esensial adanya bentuk penghormatan kepada leluhur merupakan kelanjutan tradisi megalitik pada masa prasejarah. Disimpulkan, pada masa pengaruh Islam kehidupan religi khususnya yang berkaitan dengan kematian terdapat suatu reduksi dengan masa pra Islam.